Fibroadenoma with pseudo angiomatous stromal hyperplasia and hamartoma of the breast: a case report - Ahmed, Qazi N.; Chand, Syed O.; Patel, Riyaj S.; Saquib, Hingora M. (International Journal of Research in Medical Sciences, 2025)
Pseudo angiomatous stromal hyperplasia (PASH) is an uncommon benign proliferative lesion of the breast stroma, characterized histologically by interanastomosing slit-like spaces within a dense collagenous background, mimicking vascular channels but lacking true endothelial lining. It was first described in 1986 by Vuitch, Rosen, and Erlandson, who reported nine cases of breast masses simulating vascular tumors, composed of proliferative mammary stromal tissue. Although PASH is often an incidental microscopic finding in breast biopsies, it can occasionally present as a palpable mass, particularly in premenopausal women, likely influenced by hormonal factors such as estrogen and progesterone. Fibroadenomas and hamartomas are also common benign breast entities, each with distinct histopathological features. However, the coexistence of PASH, fibroadenoma, and hamartoma within a single lesion is exceedingly rare, and its presentation with bloody nipple discharge, a symptom more often associated with intraductal carcinoma or papilloma, makes diagnosis particularly challenging. Accurately distinguishing benign from malignant lesions requires a multimodal approach, integrating clinical examination, radiologic imaging and core needle biopsy. Lesions that are classified as B3 on histopathology-including cellular fibroadenomas, papillomas with atypia, or complex sclerosing lesions-typically mandate complete surgical excision to rule out associated malignancy. This case report underscores the diagnostic complexities associated with overlapping benign breast lesions and highlights the importance of comprehensive evaluation and interdisciplinary collaboration in guiding management. Further prospective studies are warranted to optimize early detection strategies and decision-making in cases involving lesions with uncertain or mixed histology. This case emphasizes the need for a multidisciplinary approach, combining clinical, radiological, and pathological evaluations to accurately diagnose complex presentations. Recognizing rare benign lesions can prevent overtreatment and alleviate patient anxiety.